$ (a+b)^3 &= (a+b)^2(a+b)\\

&=(a^2+2ab+b^2)(a+b)\\

&=(a^3+2a^2b+ab^2) + (a^2b+2ab^2+b^3)\\

&=a^3+3a^2b+3ab^2+b^3$

New modification of Latex plugin in repository

It works with movable type 4.2 but doesn't work in rich edit mode.

$ (a+b)^3=c $

$ (a+b)^3 &= (a+b)^2(a+b)\\

&=(a^2+2ab+b^2)(a+b)\\

&=(a^3+2a^2b+ab^2) + (a^2b+2ab^2+b^3)\\

&=a^3+3a^2b+3ab^2+b^3$

New modification of Latex plugin in repository

It works with movable type 4.2 but doesn't work in rich edit mode.

$ (a+b)^3=c $

## Comments

comments powered by Disqus